Age, Body Mass Index, and Waist-to-Hip Ratio Related Changes in Insulin Secretion and Insulin Sensitivity in Women with Polycystic Ovary Syndrome: Minimal Model Analyses - Mirjana Šumarac-Dumanović; Danica Stamenković-Pejković; Danka Jeremić; Janko Dumanović; Vesna Mandić-Marković; Miloš Žarković; Dragan Micić (International Journal of Endocrinology)
Insulin resistance is believed to be an integral component of the polycystic ovary syndrome (PCOS). Beta (ß) cell dysfunction is also found in PCOS. In the study, we determined the influence of age, body mass index (BMI), and waist-to-hip ratio (WHR) on insulin response to oral glucose load (OGTT) and on insulin sensitivity (Si) and ß-cell function in young women with PCOS. One hundred fourteen patients with PCOS and 41 controls with normal basal plasma glucose were studied. A 75-g OGTT was performed to determine glucose tolerance and insulin response. Insulin sensitivity and ß-cell function were studied using a modified frequently sampled IV glucose tolerance test (FISGTT) to determine the acute insulin response (AIRG), as well as Si by minimal model analysis. Si was decreased in PCOS women (2.49 0.18 vs. 3.41 ± 0.36, p<0.05), but no difference in AIRG existed between the PCOS and control group (75.1 ± 4.6 vs. 63.4 ± 4.6, p<0.05). BMI and WHR correlated negatively with Si (r = −0.43; r = −0.289, p<0.001, respectively), but not with AIRG (r = 0.116; r = −0.02, p>0.05, respectively). Increasing age correlated negatively with AIRG (r = −0.285, p<0.001). There was a significant interaction between disease (PCOS), BMI, and WHR on Si as well as between age and PCOS on AIRG. Thus, patients below the age of 25 with PCOS showed enhanced AIRG (89.5 ± 7.1 vs. 65.1 ± 6.7, p<0.05) and decreased Si (2.43 ± 0.25 vs. 4.52 ± 0.62, p<0.05) compared to age-matched controls. In conclusion, these data suggest that not all patients with PCOS have basal and stimulated hyperinsulinemia, insulin resistance, and impaired glucose tolerance. Based on these data in young PCOS subjects, the development of insulin resistance and T2DM may be prevented with appropriate treatment strategies.